Psalms now - Brandt, Leslie F. (Concordia Pub. House, 1973)
The Psalms. Cries from isolation. Exuberant shouts of praise. Doubt and trust. Anguish, joy, and fear of the Lord. Here the psalmists' bold, free prayers become yours in the words and phrases and look of today. - Jacket flap.